Unequal andunstable: income inequality and bank risk - Yuliyan Mitkov; Ulrich Schüwer (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
We document that the dispersion of failure risk across banks within a given region in the U.S. is greater in regions that have higher income inequality. We explain this pattern with a model based on risk shifting incentives where banks issue insured deposits and choose the riskiness of their portfolios. In equilibrium: (i) some banks endogenously specialize in safe lending, while others engage in risk shifting and (ii) a competition to risk shift emerges whereby loans to subprime borrowers carry negative NPVs. The dispersion of bank risk generated by this sorting is magnified in more unequal regions with greater subprime credit segments.
Keywords: G11; G21; G28; G51; 330; Inequality; Financial stability; Agency costs; Composition of credit; Banking competition